Corneal opacities after small-incision lenticule extraction. Issue 9 (September 2022) - Hjortdal, Jesper; Daya, Sheraz; Kweon Kim, Eung; Sekundo, Walter; Ganesh, Sri; Brar, Sheetal; Moshirfar, Majid; Hansen, Annika M.; Payne, Carter J.
Abstract : A 36-year-old woman was referred to our clinic in October 2021 with suboptimal vision at intermediate and near distances and halos and photophobia after a small-incision lenticule extraction in December 2019. Abstract : A 36-year-old woman was referred to our clinic in October 2021 with suboptimal vision at intermediate and near distances and halos and photophobia after a small-incision lenticule extraction (SMILE) in December 2019. The patient needs to increase font size of her computer to 150% to read text, but images still appear blurred. She indicates that sunglasses seem to improve her contrast. Preoperatively, her refractive error was −2.5 diopters (D) and −2.25 D for right and left eyes. The optical zone size of the SMILE procedure was 6.8 mm. There is no further information available on the peroperative course of the SMILE procedure. Her uncorrected distance visual acuity (UDVA) is 20/20 in both eyes and does not improve with correction. The Schirmer tear test is 14 to 13 mm. Slitlamp biomicroscopy of the right eye and the left eye reveals hyperreflective small opacities in the anterior one-third of the corneal stroma (Figures 1 and 2 ). No other abnormalities are seen. The scotopic pupil sizes are 6.41 and 6.73 mm. Straylight measurements are within normal limits. Higher-order aberrations (HOAs) measure for the right eye (6.03 mm pupil) 0.818 μm and for the left eye (6.17 mm pupil) 0.560 μm. The corneal Scheimpflug tomography quad maps for both eyes are shown in Supplemental Figures 1 and 2 (http://links.lww.com/JRS/A663, http://links.lww.com/JRS/A664 ). What is your diagnosis or are additional diagnostic methodologies needed to establish a diagnosis? What is your treatment advice for this patient?